Techno-economic analysis of the sequential recovery of valuable metals from waste tantalum capacitors in Indian context - Agrawal M.; Singh R.; Singh K.K. (My University, 2025)
The necessity for urban mining of metals has arisen due to the growing demand for metals brought about by technological innovation, the depletion of natural resources, and the exponential growth in e-waste generation. However, to be industrially adaptable, any recycling process must be economically profitable. Therefore, in this article, an economic feasibility study was conducted to determine the profitability of the proposed recycling process for recovering valuable metals from waste tantalum capacitors. Firstly, an integrated process was developed for the recovery of almost all economically and strategically significant metals. A detailed elemental and metallurgical balance followed this to determine the mass flow of metals during various stages of treatment. Lastly, the economic feasibility analysis has been done by estimating various cost components from capital and operating costs (utilizing Indian cost as foundation for calculation) to evaluate the profit that might be made by operating the suggested recycling facility for a month. Sensitivity and scenario analysis further investigated the impact of the most significant cost component on the percentage profit. The findings of this study support the notion that the suggested recycling method has a great deal of potential value and is commercially feasible with an ample profit margin. © 2023 The Institution of Chemical Engineers